Using the apparent volume parameter to estimate rock mass damage - Dunlop, R; Parraguez, R; Zepeda, R (Caving 2010: Second International Symposium on Block and Sublevel Caving, 2010)
The apparent volume seismic parameter has been defined as an estimation of the volume of rock with coseismic inelastic strain. The spatial distribution of this parameter can be understood as a measurement of the rock mass coseismic deformation. A first stage to use this parameter is to calibrate it regarding the observed damage. For this purpose, the damage affecting the existing galleries located in the volume with a seismic response has to be recorded. Then, a spatial distribution of the parameter is achieved. The observed damage is related to the range of apparent volume values obtained at the location of interest. In that way, the values of the apparent volume parameter can be used to estimate the damage generated to the rock mass in the volumes where a direct observation is not possible. This paper describes how this approach was use at the El Teniente Mine.